Scanning probe microscopy in industrial applications : nanomechanical characterization - Yablon, Dalia G., 1975- (Wiley, 2014)
"Covering a diverse range of practical applications and real-world examples, Scanning Probe Microscopy for Industrial Applications examines important and successful applications of SPM in various industries, including food science, personal care industry, and forestry applications. Author D. G. Yablon details how SPM has impacted the industrial sector leading to improved product formulation, new understanding of processes, and improvements in manufacturing. The book provides chemists, materials scientists, physicists, polymer scientists, and biophysicists with the most important and successful applications of SPM"--Resumé vydavatele
Keywords: skenovací mikroskopie; mikroskopické zkoumání materiálů; nanomechanika; scanning probe microscopy; microscopic examination of materials; nanomechanics; kolektivní monografie; collective monographs